An Ushuliyyah Perspective on the Status of Children Born Out of Wedlock : (Critical Reasoning on the Decision of the Constitutional Court of Indonesia No. 46 of 2010 Regarding the Status of Children Born Out of Wedlock) - Khusnul A'in, Aprilianita (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2024)
This paper arises from the controversy surrounding the Constitutional Court's Decision No. 46/PUU-VIII/2010 regarding the status of children born out of wedlock. The author believes that the polemic surrounding this decision necessitates an analysis using a Ushuliyyah (Islamic legal theory) approach to determine whether the decision aligns with the principles of justice in Shari'ah or not, as Shari'ah also upholds the values of justice and public welfare. The type of research conducted is a document-based study (library research) with a combined approach, both theoretical and documentary. The primary source of data is the Constitutional Court's Decision No. 46/PUU-VIII/2010, while the secondary sources include all documents such as books, writings, interviews, and other materials related to the research subject. These data were then analyzed using descriptive analysis methods. The research results indicate two important points: First, the Constitutional Court's Decision No. 46/PUU-VIII/2010 is consistent with the concept of public welfare (maslahatul aulad) in terms of living expenses, education, health, and other aspects, except for civil rights related to lineage, guardianship, and inheritance, as there is no legal ruling by Shari'ah, nor any evidence prohibiting it. Second, according to the concept of istishan istitsna'i (exceptional preference), which involves making exceptions to general rules based on specific evidence, a child born out of wedlock does not have a Shari'ah-recognized lineage relationship with their biological father or the biological father's family.